Solve for y 6=6y-12

Math
6=6y-12
Rewrite the equation as 6y-12=6.
6y-12=6
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 12 to both sides of the equation.
6y=6+12
Add 6 and 12.
6y=18
6y=18
Divide each term by 6 and simplify.
Tap for more steps…
Divide each term in 6y=18 by 6.
6y6=186
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6y6=186
Divide y by 1.
y=186
y=186
Divide 18 by 6.
y=3
y=3
Solve for y 6=6y-12

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top